Percentage points for testing homogeneity of several bivariate Gaussian populations (2014)
ABSTRACT: In this article, the exact distribution and exact percentage points for testing equality of q bivariate Gaussian populations are obtained. The distribution has been derived using the inverse Mellin transformation and the residue theorem. The percentage points have been computed for q = 2(1)5.